Spatial Variation of Tropical Urban Carbon Dioxide Concentration: A Case Study of KualaLumpur - Nayan, Nasir; Hashim, Mohmadisa; Saleh, Yazid; Mahat, Hanifah; Luyan, Madeline Henry; Zaky, Nur Suhaila Mohd (International Journal of Psychosocial Rehabilitation, 2020)
Many of the studies related to air pollution in urban areas also consider the role of carbon dioxide (CO2) in determining the level of urban air pollution, especially in urban areas with high rates of motor vehicle use. Therefore, this study aimed to study the level of carbon dioxide concentration in the city of Kuala Lumpur by looking at the patterns of carbon dioxide concentration in the room at night and during the day. The study results and the steps to reduce this amount of CO2 can be done in the right place. This study uses data collected from field studies with Handled Temp / RH / CO2 tools to obtain carbon dioxide concentration data in six urban zones of Kuala Lumpur. Each zone will be represented by two sampling stations whose criteria are in the urban area and not in the open area. For this reason, most of the stations selected are in the open parking area. Sampling times are at night (1-4am) and daylight (1-4pm). Descriptive statistics and regression interpolation are used with the help of geographic information system software ArcGIS version 9.3. The findings showed that the average concentration of carbon dioxide at station 1 (Dataran Merdeka) was highest at night with an average reading of 458.125 part per million (ppm), and during the day, its reading was 420.125 ppm. The lowest carbon dioxide concentration was at night at Station 11 (Tesco extra Cheras) at 396 ppm and during the day at station 10 (Bukit Jalil Stadium) at 397.625 ppm. The overall average for night and day was at Station 1 at 436.31 ppm and Station 10 with a mean of 396.5 ppm. Carbon dioxide concentration levels were determined based on previous studies. The highest levels were 415.26 ppm, medium-high 401 ppm to 415.25 ppm, and the lowest was 400 ppm. It is found that urban zones have the highest levels of carbon dioxide concentration compared to other zones.In conclusion, this station needs to be reduced in carbon dioxide as it can have adverse effects if not curbed as it impairs health and can lead to increased greenhouse gases. Effective steps need to be taken so that carbon dioxide emissions can be controlled and minimized and to address the problem of global warming. The study implies that in Kuala Lumpur, the concentration of carbon dioxide is at a relatively high level.